An observational study of antibiotic prescription in management of urinary tract infection in the Arabian Gulf. (September 2019) - Bagheri, Fariborz; Al Baha, Ziad GM; Panackal, Arun; Abraham, Mathew
Objectives: The aim of this study was to describe antibiotic prescription for management of urinary tract infections (UTIs) in daily clinical practice in the Arabian Gulf and to compare prescription patterns with the recommendations of different recent guidelines. Method: This was a multicentre, cross-sectional, observational study evaluating antibiotic prescription in the management of UTIs in five countries from the Arabian Gulf. Randomly selected physicians who routinely treat patients with UTIs enrolled consecutively adult patients prescribed an antibiotic for treatment or prophylaxis of a UTI. Data were collected on UTI symptoms, antibiotic prescription, co-medications and relevant diagnostic laboratory tests. Results: Fifty physicians enrolled 522 eligible patients. The reason for antibiotic prescription was treatment of a UTI in 502 patients, and prophylaxis in 20 patients. The most frequent types of UTI documented were cystitis (301 cases) and urethritis (143 patients). Overall, the most frequently prescribed antibiotics for treatment of active UTIs were levofloxacin (344 patients; 68.7%), ciprofloxacin (69 patients; 13.8%) and ceftriaxone (34 patients; 6.8%). The pattern of antibiotic prescription was essentially similar irrespective of the indication. Only six patients with uncomplicated acute cystitis received the treatment recommended as first choice in the European Association of Urology or Infectious Diseases Society of America and European Society of Clinical Microbiology and Infectious Disease guidelines (nitrofurantoin or trimethoprim/sulfamethoxazole). Conclusions: We observed pronounced divergence from international practice guidelines for the use of antibiotics for the treatment or prophylaxis of UTIs in the Arabian Gulf, even though most participating physicians, and essentially all urologists, claimed to be familiar with them. In this context, the development and diffusion of regional practice guidelines may be particularly useful. Level of evidence: Not applicable for this multicentre audit.